Luisa Elena Delgado, Pura Fernández, and Jo Labanyi, eds. Engaging the Emotions in Spanish Culture and History. Vanderbilt UP, 2016. - Olga Bezhanova (Studies in 20th & 21st Century Literature, 2018)
Review of Engaging the Emotions in Spanish Culture and History. Eds. Luisa Elena Delgado, Pura Fernández, and Jo Labanyi. Nashville: Vanderbilt UP, 2016. ix + 300 pp.
Keywords: emotions; Spanish Civil War